Microeconomic theory - Dwivedi, D. N. (Delhi : Vikas publishing house PVT Ltd., 1987)
They are propositions that are motivated by economic reality as observable, not to mention controllable, as that may be, but they are no more and no less than comments about that economic reality and they emphatically are not descriptive assays of it.
Includes bibliographical references and index.
aia 14/05/2018
Loans
Keywords: Microeconomics